2019
DOI: 10.1186/s40659-018-0208-1
|View full text |Cite
|
Sign up to set email alerts
|

ErbB1 and ErbB3 co-over expression as a prognostic factor in gastric cancer

Abstract: BackgroundEpidermal growth factor receptor family members such as ErbB1 and ErbB3 are involved in tumor progression and metastasis. Although, there are various reports about the prognostic value of EGFR members separately in gastric cancer, there is not any report about the probable correlation between ErbB1 and ErbB3 co-expression and gastric cancer prognosis. In present study, we assessed the correlation between ErbB1 and ErbB3 co-overexpression (in the level of mRNA and protein expression) and gastric cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…There are about ninety TKs in human genome which are involved in various cellular processes such as differentiation, metabolism, motility, and proliferation [17,18]. Receptor tyrosine-kinases are up regulated in various tumors and are considered to be potential oncogenes involved in cancer initiation and development [19,20]. Therefore, targeting these oncogenes and inhibiting their expression may result in good clinical outcomes [21].…”
Section: Introductionmentioning
confidence: 99%
“…There are about ninety TKs in human genome which are involved in various cellular processes such as differentiation, metabolism, motility, and proliferation [17,18]. Receptor tyrosine-kinases are up regulated in various tumors and are considered to be potential oncogenes involved in cancer initiation and development [19,20]. Therefore, targeting these oncogenes and inhibiting their expression may result in good clinical outcomes [21].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the mechanism about how the HER2-mTOR signal pathway-mediated autophagy regulates the tumorigenicity of GCSCs will be investigated in the following researches. In this manuscript, although others have demonstrated that co-overexpression of ErbB1 and ErbB3 can be used as a prognostic factor in GC ( 33 ), we did not examine the correlation among the expression of ErbB1 and ErbB3 of gastric stem cells because some published studies have demonstrated that adding the agents targeting the ErbB1 or ErbB3 to chemotherapy does not improve overall survival or disease control rate compared with chemotherapy alone in clinical practice ( 34 , 35 ), while Trastuzumab targeting the HER2 in combination with chemotherapy could improve the overall survival of patients with advanced GC ( 4 ). Therefore, we focused on investigating the role of HER2 in self-renewal, invasion, and tumorigenicity of GCSCs.…”
Section: Discussionmentioning
confidence: 89%
“…Molecular typing of GC also has an important role in the prognosis of patients ( 35 ). In recent years, an increasing number of studies have reported that certain factors, including high co-overexpression of epidermal growth factor receptor and receptor tyrosine kinase 3, low levels of microRNA-214 and high methylation of RASSF10, are associated with poor prognosis in patients with GC ( 30 , 36 , 37 ). In the present study, the peripheral NK cell levels were determined to be an independent prognostic factor in patients with GC and patients who died within 5 years had a higher level of peripheral NK cells.…”
Section: Discussionmentioning
confidence: 99%